Ocean-Atmosphere interactions in the mid-Pliocene global warming: Lessons for the 21st century climate - Pontes, Gabriel Marques (2022)
During the mid-Pliocene (~3 million years before present), annual mean temperatures were approximately 3°C higher than present, which is similar to the projected global warming for the end-of-century climate. Furthermore, carbon dioxide (CO2) concentrations in the atmosphere were similar to present day (~400 ppm). Paleoclimate studies have been investigating whether there was a past warm climate that would serve as an analogue for the current warming. As such, the mid-Pliocene climate arises as a candidate to a possible future scenario. This thesis investigates key aspects of the Southern Hemisphere climate in the mid-Pliocene through the simulation results of the Pliocene Model Intercomparison Project and climate model sensitivity experiments to evaluate whether the mid-Pliocene is comparable to the projected future warming. Firstly, higher rates of warming in the northern hemisphere create an interhemispheric temperature gradient that enhances the southward cross-equatorial energy flux by up to 48% in the mid-Pliocene. This intensified energy flux reorganizes the atmospheric circulation leading to a northward shift of the Inter-Tropical Convergence Zone (ITCZ) and weakened and poleward displaced Southern Hemisphere Subtropical Convergences Zones. These changes result in drier-than-normal Southern Hemisphere tropics and subtropics, with rainfall reductions in South America of up to 25%. Second, the modes of variability based on Atlantic sea surface temperature were overall weaker and less frequent, indicating increased climate stability in the mid-Pliocene. In particular, a weaker Atlantic Meridional Mode was associated with increased inter-hemispheric SST gradient and northward ITCZ shift. Lastly, a northward shift of the Pacific ITCZ reduced the activity of the El Niño Southern Oscillation by 25%. These results highlight the key role of the ITCZ position in driving climate change in the tropics and subtropics of the Southern Hemisphere. Observations and numerical studies of the ongoing warming, on the other hand, show a southward shift in the Pacific and Atlantic ITCZs, which indicate that the mid-Pliocene global warming differs from the current warming. Thus, significant climate aspects represented by the current set of Pliocene climate simulations are not being experienced in 20th/21st century warming of the planet. Nonetheless, this thesis highlights the effects of meridional shifts of the ITCZ to the Southern Hemisphere climate.